Sinergi Teologi Dan Ilmu Medis Dalam Eksplorasi Kasus Kerasukan Di Dunia Pelayanan Pastoral - Adiatmo, Kumoro; Dully, Stefanus; Dyna R.D, Hildegardis; Simon (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2024)
It has drawn public attention and sparked debates about the boundary between mental disorders and spiritual phenomena. This study explores the synergy between theology and medical science in addressing cases considered as possession in the realm of pastoral care. Using a qualitative approach and literature review method, the research analyzes the need to integrate theological and medical approaches and identifies effective ways of integration in pastoral care. The findings of this study indicate that a proper integration of theological and medical understanding can create a more holistic and comprehensive approach to handling possession cases. The research also emphasizes the importance of collaboration between pastoral caregivers and medical professionals to reduce the risk of handling errors that could endanger individuals. This study is expected to make a significant contribution to bridging the gap between theological and medical approaches, as well as enhancing the quality of safe and effective pastoral care.